UGT1A1 Polymorphism for Irinotecan Dose Escalation in Patients with BRAF-Mutated Metastatic Colorectal Cancer Treated with First-Line Bevacizumab and FOLFIRI. (11th March 2021) - Hsieh, Yi-Chien; Chang, Tsung-Kun; Su, Wei-Chih; Huang, Ching-Wen; Tsai, Hsiang-Lin; Chen, Yen-Cheng; Li, Ching-Chun; Chen, Po-Jung; Yin, Tzu-Chieh; Ma, Cheng-Jen; Wang, Jaw-Yuan
Abstract : Background . Patients with metastatic colorectal cancer (mCRC) and BRAF V600E mutation have a poor prognosis, with a median progression-free survival (PFS) of only 5–7 months after initial therapy. The current standard first-line chemotherapy for these patients includes FOLFOX or FOLFIRI plus bevacizumab. In this study, we explored the effects and oncological outcomes of UGT1A1 polymorphism for irinotecan escalation in patients with BRAF- mutated mCRC. Patients and Methods . This retrospective study included 17 patients with BRAF- mutated mCRC between April 2016 and December 2019. UGT1A1 genotyping was performed on all patients prior to initiating bevacizumab plus FOLFIRI chemotherapy. The primary endpoint was PFS, and the secondary endpoints were toxicity, response rate, disease control rate, and overall survival (OS). Results . Fifteen and two patients had UGT1A1 1∗/1∗ and 1∗/28∗, respectively. Eight underwent irinotecan dose escalation with tolerable adverse effects (AEs), and nine maintained an irinotecan dose of 180 mg/m 2 or required deescalation to 150 mg/m 2 due to intolerable AEs. After a median follow-up period of 15.7 (range, 3–54) months, the median PFS and OS were 9.4 and 15.7 months, respectively. Grade 3/4 AEs were observed in three (6%) patients. The disease control and partial response rates were 64.7% and 11.8%, respectively, indicating that most patients (14, 82.3%) could maintain this as a first-line line therapy with stable disease or proceed to second-line therapy if disease progression occurred, thereby maintaining acceptable performance status. Conclusions . The oncological outcomes of patients with BRAF- mutated mCRC treated using FOLFIRI plus bevacizumab with irinotecan dose escalation as a first-line therapy are acceptable with tolerable AEs; this may be a feasible treatment option in such patients. Pretherapeutic UGT1A1 genotyping-guided dose adjustment can achieve favorable outcomes.